Understanding interpersonal data management in the home - Kilic, Damla (2023)
The home is a place where personal data is increasingly collected and used, whether online or through connected devices, commensurate with the development of new data protection regulations and technology initiatives to create privacy-enhancing technologies (PETs). However, they focus on personal data and miss the interpersonal nature of data that cannot be attributed to individuals. This thesis aims to understand the interpersonal nature of personal data and the challenge of collaborative rather than individual data management in the domestic context in which a great many future ‘smart’ consumer services will be situated to inform the development of future technologies that enable the social management of personal data. Two empirical studies using multiple qualitative methodologies were conducted to address the aim of this thesis.